2017
DOI: 10.12783/dtem/apme2016/8781
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Opinion Leaders towards Consumer Information Adoption in the Virtual Communities of Consumption

Abstract: With the appearance and popularity of virtual communities of consumption, potential consumers begin to search for and share information with others in such kind of platforms and to be affected by the electronic word of mouth of certain products or services. Meanwhile, opinion leaders begin to exert influence on these individuals by helping them to filter, categorize and figure out the most valuable pieces of information. Consequently, how to utilize opinion leaders to affect consumer behavior by term of electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 23 publications
(25 reference statements)
0
2
0
13
Order By: Relevance
“…They are either experts in a specific area of knowledge, or have a wide range of social connections [14]. Previous research has identified several characteristics of KOLs, namely that they are professionals, innovative, involved, and sociable [36]. Moreover, [37] demonstrated several characteristics in determining KOLs: they must be knowledgeable in their field, respected by their audience, have wider access to information sources than their followers, and lastly, have the ability to maintain their leadership.…”
Section: B Key Opinion Leaders (Kols)mentioning
confidence: 99%
See 1 more Smart Citation
“…They are either experts in a specific area of knowledge, or have a wide range of social connections [14]. Previous research has identified several characteristics of KOLs, namely that they are professionals, innovative, involved, and sociable [36]. Moreover, [37] demonstrated several characteristics in determining KOLs: they must be knowledgeable in their field, respected by their audience, have wider access to information sources than their followers, and lastly, have the ability to maintain their leadership.…”
Section: B Key Opinion Leaders (Kols)mentioning
confidence: 99%
“…Moreover, [37] demonstrated several characteristics in determining KOLs: they must be knowledgeable in their field, respected by their audience, have wider access to information sources than their followers, and lastly, have the ability to maintain their leadership. According to [36], KOLs can be generally categorized into two types: the ones who are active offline such as public figures and celebrities, and thus can easily become online opinion leaders. And those who share their opinions online exclusively.…”
Section: B Key Opinion Leaders (Kols)mentioning
confidence: 99%
“…Penelitian pada konteks online marketing menyatakan bahwa rekomendasi dari opinion leaders dapat memengaruhi kepercayaan pada merk, meningkatkan engagement, dan niat beli konsumen atau calon konsumen potensial (Aghdam & Navimipour, 2016;Ananda, 2018;Chu & Kim, 2011;Cooley & Parks-Yancy, 2019;Gefen et al, 2003;Haron et al, 2016;Lafferty et al, 2002;H.-C. Lin et al, 2018;X. Lin et al, 2019;Listyorini, 2015;Lu et al, 2010;Nunes et al, 2018;Oestreicher-Singer & Zalmanson, 2013;Raghupathi & Fogel, 2015;Schouten et al, 2020;Wang, 2017;Wardhana, 2016). Pada situasi krisis, opinion leaders juga memiliki peran dalam memengaruhi kepercayaan orang lain terhadap suatu informasi mengenai bencana atau krisis yang sedang terjadi (Hagar, 2013;Wardyaningrum, 2018).…”
Section: Pendahuluanunclassified
“…Menurut Turcotte et al (2015), kepercayaan dapat meningkat karena adanya peran dari opinion leaders dalam merekomendasikan atau menyebarkan informasi, konten, atau berita. Sedangkan Wang (2017) berpendapat bahwa kredibilitas sumber adalah sejauh mana orang-orang mempertimbangkan sumber informasi, yaitu opinion leaders yang kompeten dan reliabel. Maka influencers atau opinion leaders memiliki peran yang sama sebagai sumber informasi (Lou & Yuan, 2019).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation